Treatment of nervous complaints and exhaustion with the homeopathic medicinal product Manuia® - results of a cohort study - Wilkens, J.; Klement, P. (Homeopathy, 2014)
Background: Exhaustion, nervousness and decreased physical and mental capability are recurrent challenges in GPs’ daily routine. They are often resulting from overexertion, or disturbed sleep. Nowadays people feel exhausted and weak due to continuously increasing professional demands and rising challenges in daily life. The approved homeopathic medicinal product Manuia is used in the mentioned therapeutic area. It contains four single active substances: Damiana, Panax ginseng, Acidum phosphoricum and Ambra. So far, effectiveness and tolerability was confirmed by clinical experience, but systematically collected data were lacking.Patients and methods: Between January and June 2011 the clinical effectiveness and tolerability of Manuia was systematically investigated in a prospective, multicentre, non-interventional cohort study. A total of 420 patients were observed by 76 German physicians in private practices. Median observation period was 24 days, median duration of symptoms since diagnosis 5 months.As main outcome measure severity course of 20 symptoms (nervousness, irritability, sleep disturbances, hyperactivity, impaired concentration, listlessness, frustration, moroseness, exhaustion, dispiritedness, decreased capability, feeling of heteronomy, feeling lonely, feeling pressure to perform, feeling excessive demands, forgetfulness, gastrointestinal complaints, cardiovascular complaints, muscle tension, headache) was evaluated with a 5-item score (0 = not present; 4 = very severe). In addition physicians’ Clinical Global Impression (CGI), patients’ quality of life and ability to actively attend different domains of daily's life, and tolerability of Manuia were documented.Results: The sum score as well as the severity of each single symptom decreased significantly during the observations’ period (p<0.01, paired t-test). Illness severity measured by CGI decreased significantly (p<0.01, McNemar test; CGI 4-7: 71.7% to 35.2%). Ability to work and to attend social and family life improved significantly (p<0.01, McNemar test). In 77.1% (n=324 out of 420) of the patients quality of life was good, very good or excellent during control visit, compared to 15.8% (n=66 out of 420) at baseline. 92.4% of the patients rated their condition as improved, 64.1% as much or very much improved. Median duration until onset of action was 7 days. Tolerability was good or very good in 98.1% of all cases.Conclusion: The study data underlined the existing good clinical experience with Manuia and suggests Manuia as a therapeutic option in the treatment of nervous complaints and exhaustion. Further controlled studies are necessary to confirm these findings.